2012
DOI: 10.5153/sro.2687
|View full text |Cite
|
Sign up to set email alerts
|

The Neoliberal Phoenix: The Big Society or Business as Usual

Abstract: At present something curious appears to be occurring in the UK in the aftermath of the ‘credit crunch’, with respect to the political, economic and social complexion of the policies currently being implemented by the Coalition government, and not least in terms of the manner in which they are being introduced. Specifically, as this paper argues, despite a degree of rhetoric to the contrary, asserting a movement towards a more socially ‘progressive’ and inclusive ‘Big Society’, the current policy framework appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For Bone (2012), the Big Society represents less a call for people to build a stronger society and more of a charter for government to abdicate from its responsibilities to support and defend its citizens. Thus Bone is echoing Clarke's analysis of citizenship under New Labour where he concluded that under New Labour activated law-abiding citizens were empowered with greater responsibility to eschew anti-social behaviour in order to promote harmony, as a requirement of citizenship, in exchange for increased abandonment as the state systematically divested itself of its responsibilities to safeguard citizens (Clarke 2005).…”
Section: The Young Offender As Adult Citizenmentioning
confidence: 99%
“…For Bone (2012), the Big Society represents less a call for people to build a stronger society and more of a charter for government to abdicate from its responsibilities to support and defend its citizens. Thus Bone is echoing Clarke's analysis of citizenship under New Labour where he concluded that under New Labour activated law-abiding citizens were empowered with greater responsibility to eschew anti-social behaviour in order to promote harmony, as a requirement of citizenship, in exchange for increased abandonment as the state systematically divested itself of its responsibilities to safeguard citizens (Clarke 2005).…”
Section: The Young Offender As Adult Citizenmentioning
confidence: 99%
“…It is suggested that the categorization of particular forms of drinking as problematic is shaped by a specific neoliberal ‘mentality of government’, which also circumscribes the publicly debated policy options. This is a notably different argument from that presented by Bone (2012), for example, who argues that the ‘Big Society’ risks being little more than a cover to rehabilitate neoliberalism in the wake of the financial crisis. In alcohol policy, to quote Bone, it can reasonably be said to be ‘business as usual’, without even the cover of ‘Big Society’ ideas.…”
Section: Introductionmentioning
confidence: 77%
“…By the time the PLINY intervention was being delivered it had become difficult to talk about voluntary work in the UK without reference to the 2010 government's Big Society policy, a stated objective of which is 'a society where people come together to solve problems and improve life for themselves and their communities'. 88 This policy has had its detractors in the academic literature with some seeing it as ineffective [89][90][91][92][93][94] and others going further, accusing it of providing rhetorical cover for an agenda of spending cuts, privatisation and regressive taxation that will increase inequality, [95][96][97][98] DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk not least because small-scale voluntary sector organisations are thought to have been most seriously compromised by the deficit reduction programme. 99 Our study provides limited evidence that some individuals who might previously have volunteered are deterred by an association with a political agenda that they eschew, which adds to an ongoing debate about whether such policies are eroding confidence in the third sector.…”
Section: Other Studies Involving Volunteer Provisionmentioning
confidence: 99%